The use of herbal medicines as slimmings in a city of Maranhão (Research, Society and Development, 2020)
Evaluate the use of herbal medicines as weight loss in the population of the interior of Maranhão. Retrospective descriptive exploratory study, from January 2017 to December 2018, where all the herbal products sold in the period were researched and those used as weight loss were identified. There was a decrease in the total of 2018 compared to 2017, the General Herbal Medicines were better sold, with about 90.57% and 9.43% of Slimming Herbal Medicines. The proportion in 2018 did not change significantly, being 95.65% of General and 5.35% of Weight Loss. The months of 2017 where there were more dispensing slimming herbal medicines were: May, August, June, July. In 2018, the most sold months were: January, October, February and August respectively. The use of herbal medicines without medical advice, although consumption has decreased between the two years, has not reduced the risks that weight loss can cause in the health of these users, since most have not done health checks regularly, don't make proper diets, among other reasons that influence the drug.